Bioactive compounds in Hericium erinaceus and their biological properties: a review - Yue Qiu; Genglan Lin; Weiming Liu; Fuming Zhang; Robert J. Linhardt; Xingli Wang; Anqiang Zhang (Food Science and Human Wellness)
Hericium erinaceus is a nutritious edible and medicinal fungi, rich in a variety of functional active ingredients, with various physiological functions such as antioxidation, anticancer, and enhancing immunity. It is also effective in protecting the digestive system and preventing neurodegenerative diseases. In this review paper, we summarize the sources, structures and eff icacies of the main active components in H. erinaceus fruiting body, mycelium, and culture media, and update the latest research progress on their biological activities and the related molecular mechanisms. Based on this information, we provide detailed challenges in current research, industrialization and information on the active ingredients of H. erinaceus. Perspectives for future studies and new applications of H. erinaceus are proposed.